2015
DOI: 10.1515/tperj-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen effect on reaction speed and lower limbs power

Abstract: Background:Acetaminophen (also known as Tylenol or Paracetamol) is a very popular drug, that requires no prescription and is usually used as analgesic and antipyretic. A considerable number of previous studies show that acetaminophen has no effects that could alter exercise capacity or performance. Onthe other hand, there are studies sustaining that exercise performance can be improved with acetaminophen through a reduction in perceived pain, and also a reduction of the body heat produced by the muscle contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Its effects, which are likely to impact sporting performance, especially by suppressing the perceived pain, mean that the results from numerous studies evaluating these effects are followed with great interest by the entire sports community. Some studies have demonstrated its favourable impact on performance (Park et al, 2016, Strava & Rusu, 2015, while others have not confirmed such an effect (Delextrat et al, 2015, Mauger et al, 2010. At the same time, it should be remembered that if the studies show improvement of sport performance (Park et al, 2016, Strava & Rusu, 2015, they involve a quantity with adverse effect on the athlete's health (Hodis, 2015, Blieden et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its effects, which are likely to impact sporting performance, especially by suppressing the perceived pain, mean that the results from numerous studies evaluating these effects are followed with great interest by the entire sports community. Some studies have demonstrated its favourable impact on performance (Park et al, 2016, Strava & Rusu, 2015, while others have not confirmed such an effect (Delextrat et al, 2015, Mauger et al, 2010. At the same time, it should be remembered that if the studies show improvement of sport performance (Park et al, 2016, Strava & Rusu, 2015, they involve a quantity with adverse effect on the athlete's health (Hodis, 2015, Blieden et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated its favourable impact on performance (Park et al, 2016, Strava & Rusu, 2015, while others have not confirmed such an effect (Delextrat et al, 2015, Mauger et al, 2010. At the same time, it should be remembered that if the studies show improvement of sport performance (Park et al, 2016, Strava & Rusu, 2015, they involve a quantity with adverse effect on the athlete's health (Hodis, 2015, Blieden et al, 2014. This is why we decided to evaluate the effect of the "medically still acceptable dose" of paracetamol, reinforcing its analgesic effect by adding ASA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation